Media Learning About the Structure of Movement in the Gunungsari Mask Dance of Tumpang District - Wahyu Widyawati, Ika; Septiani, Kiki (KnE Social Sciences, 2023)
This study examines the structure of the Gunungsari mask dance movement at the Setyo Utomo dance dtudio in Glagahdowo hamlet, which in its development is rarely in demand by the younger generation because of the rare material and rarely exposed. This research can be used as a new insight in traditional dance vocational studies. The Gunungsari mask dance has a characteristic in every movement that must be introduced to the wider community, especially to students. The authors aim to describe the structure of the Gunungsari mask dance movement which can be used as an introduction to the arts of the Tumpang area for SMPN 1 Tumpang. The research method was used in the form of a descriptive qualitative approach. The research data was obtained through observation to determine the structure of movement in the dance, while interviews were conducted with four different speakers. The documentation technique was carried out using previous documents regarding the structure of the Gunungsari mask dance movement at the Setyo Utomo dance studio in Glagahdowo hamlet. The results of this study show that the motion structure of the dance is divided into three parts, namely the opening motion (which begins with the Mentang Gendewa movement), the core motion (starting with the Singget Mundur Kebyok Ghelap movement), and the closing motion (starting with the Backward Singget movement). It is hoped that this research can be used as one of the learning materials, as well as a reference to add insight to the vocational dances of the Malang area. Keywords: motion structure, Gunungsari mask dance, learning media